Maternal Stressors and Coping Strategies During the Extended Postpartum Period: A Retrospective Analysis with Contemporary Implications - Lorraine O. Walker; Nicole Murry (Women's Health Reports, 2022)
Background: Despite recent emphasis on the ?fourth trimester? and beyond, most knowledge of stressors affecting women is focused on the first 6 postpartum weeks. Our aim was to identify postpartum-specific stressors and coping over the extended postpartum period. Methods: We analyzed data from two surveys for a combined sample of 346 postpartum women. Principal components analysis of survey items on sources of stress was used to identify categories of postpartum-specific stressors. Content analysis was used to categorize text data on coping strategies. Results: Seven stressors were identified: Overload, Working mother concerns, Isolated motherhood, Limited supportive resources, Exhaustion, Parenting demands, and Changes in body and sexuality. Overload was the most frequent stressor (F?=?49.32, p?<?0.001) and was significantly higher at 9?12 months than at 5?8 months or at 13 months or more (F?=?6.42, p?=?0.002). Fulltime employment and having more than one child were associated with elevated scores on several stressors. Content analysis yielded seven coping strategies, such as Take time alone or with others, Manage emotions and thoughts, and Maintain a manageable workload. Five of the seven stressors were associated with at least one of the top five coping strategies; none was associated with Overload or Limited supportive resources. Conclusions: Women's predominant source of stress was from overload and was highest at 9 to 12 months postpartum. Community resources and public health policy and programming are needed to prepare and support women during the challenging first postpartum year.